The Role of Professional Education and Networking in the Development of Tax Professionals: The Case of DIZI - Raspor Josipovič, Črtomir; Marič, Miha (Celovita pot izobraževanja: Od ideje do mreženja, 2026)
Continuing professional education (CPE) in regulated professions often functions as a formal compliance requirement with minimal actual developmental impact. This chapter examines the role of the Tax Education Institute (DIZI), a specialized provider of professional training within the Simič & Partners Group, serving tax professionals in Slovenia. Using a mixed-methods approach we examined five dimensions of DIZI's operation: practical competence development, professional identity formation, sense of community belonging, formation of lasting professional connections, and the value of educational support services. The findings indicate that participants perceive DIZI not only as a content-rich and up-to-date provider, but also as a professional community that addresses the needs of practitioners working in micro and small organizations. The decision to return to DIZI is not primarily driven by regulatory requirements, which received the lowest scores among all measured factors, but by the quality of instructors, relevance of content, and sense of belonging. In total, 96.3% of survey respondents would recommend DIZI to others in the field. The results suggest that CPE providers generate the greatest developmental value when education, community building, and professional identity formation operate as a unified rather than purely content-driven process.